The awareness of the policyholders towards understanding the functions of insurance policy they bought: case study at Allianz General Insurance Company (Malaysia) Berhad, Kota Bharu Branch / Nurul Farhana Mohamad Nawawi - Mohamad Nawawi, Nurul Farhana (2011)
This research is about “The Awareness of the Policyholders towards Understanding the Functions of Insurance Policy They Bought: Case Study At Allianz General Insurance Company (Malaysia) Berhad, Kota Bharu Branch”. This research being done while doing practical training in industry for five months. To obtain the data, the researcher used primary and secondary data. There are 50 questionnaires being distributed randomly to the 5o respondents. The independent variables for this research are employment, education level and insurance policy and the researcher want to know whether or not these independent variables have significant and will influence the awareness of the policyholders towards understanding the functions of insurance policy they bought. Then, the researcher gets back the questionnaires from the respondents. To analyzed the data, the researcher using frequency analysis, Reliability test and Pearson Correlation. Frequency analysis used to know the frequency statistics of number of respondents answer each question in questionnaire. While, reliability test being done is to determine of the accuracy of data. Lastly is Pearson Correlation being done to know whether the research objectives have a significance or not with dependent variables. The results show that only one independent variable that is education level has significance with the dependent variable. While other two independent variables that are employment and insurance policy does not have significance with the dependent variable.